Cholesterol accelerates the binding of Alzheimer's β-amyloid peptide to ganglioside GM1 through a universal hydrogen-bond-dependent sterol tuning of glycolipid conformation - Fantini, Jacques; Yahi, Nouara; Garmy, Nicolas (Frontiers in Physiology, 2013)
Age-related alterations of membrane lipids in brain cell membranes together with high blood cholesterol are considered as major risk factors for Alzheimer’s disease. Yet the molecular mechanisms by which these factors increase Alzheimer’s risk are mostly unknown. In lipid raft domains of the plasma membrane, neurotoxic Alzheimer’s beta-amyloid (Abeta) peptides interact with both cholesterol and ganglioside GM1. Recent data also suggested that cholesterol could stimulate the binding of Abeta to GM1 through conformational modulation of the ganglioside headgroup. Here we used a combination of physicochemical and molecular modelling approaches to decipher the mechanisms of cholesterol-assisted binding of Abeta to GM1. With the aim of decoupling the effect of cholesterol on GM1 from direct Abeta-cholesterol interactions, we designed a minimal peptide (Abeta5-16) containing the GM1-binding domain but lacking the amino acid residues involved in cholesterol recognition. Using the Langmuir technique, we showed that cholesterol (but not phosphatidylcholine or sphingomyelin) significantly accelerates the interaction of Abeta5-16 with GM1. Molecular dynamics simulations suggested that Abeta5-16 interacts with a cholesterol-stabilized dimer of GM1. The main structural effect of cholesterol is to establish a hydrogen-bond between its own OH group and the glycosidic-bond linking ceramide to the glycone part of GM1, thereby inducing a tilt in the glycolipid headgroup. This fine conformational tuning stabilizes the active conformation of the GM1 dimer whose headgroups, oriented in two opposite directions, form a chalice-shaped receptacle for Abeta. These data give new mechanistic insights into the stimulatory effect of cholesterol on Abeta/GM1 interactions. They also support the emerging concept that cholesterol is a universal modulator of protein-glycolipid interactions in the broader context of membrane recognition processes.